2007
DOI: 10.1080/15376510701380422
|View full text |Cite
|
Sign up to set email alerts
|

How Sublethal Fenitrothion is Toxic in Carp (Cyprinus carpioL.) Fingerlings

Abstract: The purpose of this study was to evaluate the effects of fenitrothion, an organophosphothionate insecticide, on selected serum hematological and biochemical parameters of carp (Cyprinus carpio L.) fingerlings and investigate histopathological changes after acute dose of exposure. Among those, cortisol and glucose are evaluated as responses of early life stages of carp to acute stress and hematological blood parameters are evaluated to investigate the mechanism of toxicity via histopathological changes to the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…The level of glucose in the blood of sumithion-exposed fish increased may result from the conversion of glycogen into glucose under stressful conditions caused after sumithion exposure (Winkaler et al 2007;Hossain et al 2015;Salam et al 2015). In contrast, RBC, Hct, plasma Cl, Na, K, P and brain malondialdehyde (MDA) levels significantly decreased in common carp, Cyprinus carpio (Sepici-Dincel et al 2007). Ram and Gopal (1991) indicated that neurotransmitters norepinephrine and dopamine increased in the medulla oblongata, followed by a significant decrease in the cortex in spotted snakehead, Channa punctatus after sumithion exposure.…”
Section: Haemato-biochemical Parameters and Blood Morphologymentioning
confidence: 98%
See 2 more Smart Citations
“…The level of glucose in the blood of sumithion-exposed fish increased may result from the conversion of glycogen into glucose under stressful conditions caused after sumithion exposure (Winkaler et al 2007;Hossain et al 2015;Salam et al 2015). In contrast, RBC, Hct, plasma Cl, Na, K, P and brain malondialdehyde (MDA) levels significantly decreased in common carp, Cyprinus carpio (Sepici-Dincel et al 2007). Ram and Gopal (1991) indicated that neurotransmitters norepinephrine and dopamine increased in the medulla oblongata, followed by a significant decrease in the cortex in spotted snakehead, Channa punctatus after sumithion exposure.…”
Section: Haemato-biochemical Parameters and Blood Morphologymentioning
confidence: 98%
“…In contrast, RBC, Hct, plasma Cl, Na, K, P and brain malondialdehyde (MDA) levels significantly decreased in common carp, Cyprinus carpio (Sepici‐Dincel et al . 2007). Ram and Gopal (1991) indicated that neurotransmitters norepinephrine and dopamine increased in the medulla oblongata, followed by a significant decrease in the cortex in spotted snakehead, Channa punctatus after sumithion exposure.…”
Section: Impacts Of Sumithion On the Physiology Of Adult Fishmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous study, we evaluated the effects of sublethal toxic doses of fenitrothion (10 mg/L for 48 h) with hematologic and histopathological findings and also observed elevated levels of malondialdehyde (MDA) from the pooled liver samples [9] and concluded that fenitrothion is toxic to carp fingerlings even at sublethal doses. Also, further work should be undertaken to get a more complete picture of fenitrothion ecotoxicology and provide data for better risk assessment.…”
Section: Oo-dimethyl-o-(3-methyl-4-nitrophenyl)phosphoro-mentioning
confidence: 98%
“…But it has been emerged that, these substances which were being used for a beneficial purpose such as supplying the mankind's needs were also adversely affecting the vital functions of other living organisms such by reaching to the non-targeted organisms in time and threatening the ecological balance. Therefore, researches on environmental pollution and its effects on ecosystem due to the pesticides have gained momentum in the last few years (Adhikari et al 2004;Mgbenka et al 2005;Patnaik and Patra, 2006;Sepici-Dinçel et al 2007;Ramesh and Saravanan, 2008;Mikula et al 2008;Fırat et al 2011;Saravanan et al 2011;Jayaprakash and Shettu, 2013).…”
Section: Introductionmentioning
confidence: 99%